Factors on Zakat (Tithe) Preference as a Tax Deduction in Aceh, Indonesia - Sri Nurhayati; Dodik Siswantoro (International Journal of Nusantara Islam, 2015)
This paper aims to analyze the variables that affect zakat preference as a tax deduction. Samples are also analyzed and grouped to see some characteristics and patterns of specific issues. Structural Equation Model (SEM) is based on variance. SmartPLS is used to evaluate which variables affect the zakat preference. Samples are distributed to zakat institutions and the University in Aceh, Indonesia. Crosstab analysis can enrich the analysis of the paper. Very few people are aware of zakat as a tax deduction; however, the other  permitted regulation of zakat as a taxable income deduction has not been approved by local government. In addition, only a few people have tax numbers that are used to claim overpaid tax (restitution). Surprisingly, motivation factor significantly affects zakat preference in a negative way. On the other hand, satisfaction factor is similar to Siswantoro and Nurhayati’s 2012 findings, which is negative and insignificant. Motivation factor is positive, but insignificant.